Assessing the use of the Index of Consciousness (IoC) as a monitoring tool for the sedative effects of ciprofol during general anesthesia induction: a prospective observational study - Yanhong Yu; Hao Wang; Liguo Wei; Yifan Gao; Nuo Yan; Jing Chu; Hong Li (Perioperative Medicine)
Abstract Background We investigated the consistency and accuracy of the Index of Consciousness (IoC) and the Bispectral Index (BIS) in monitoring the sedative effect of ciprofol during the induction of general anesthesia. There is extensive literature that reports good consistency and correlations between the IoC1 and the BIS in reflecting the sedation levels induced by propofol and sevoflurane but not by ciprofol. Objective The aim was to compare the consistency and accuracy of the IoC and BIS in monitoring the sedative effect of ciprofol during the induction of general anesthesia. Methods We conducted a prospective observational study. A total of 130 patients aged 18 to 65 years who underwent noncardiac or noncranial elective surgery under general anesthesia were included. All patients were diligently monitored for both the BIS and IoC. IoC1 and BIS values were recorded at eight specific time points (T1 to T8) during the induction of general anesthesia. Bland‒Altman analysis was conducted to assess the consistency between the IoC1 and BIS, including the calculation of mean differences and 95% limits of agreement (LOAs). Receiver operating characteristic (ROC) curves were utilized to evaluate the predictive accuracy of the IoC1 for loss of responsiveness. Results The mean difference in the BIS and IoC1 values from T1 to T8 between the two measurement methods was − 0.4308 (95% LOA ranging from − 19.47 to 18.61). There was no significant difference between the IoC1 and BIS (P = 0.6664). The areas under the curve (AUCs) for the IoC1 and BIS in predicting loss of responsiveness were 0.9821 (95% CI 0.9741 to 0.9900) and 0.9855 (95% CI 0.9789 to 0.9922), respectively. The optimal threshold values were 91.5 (sensitivity 94.6%, specificity 96.0%) and 82.5 (sensitivity 99.2%, specificity 93.7%). Conclusion The IoC1 is highly consistent with the BIS in the assessment of the sedative effects of ciprofol during general anesthesia induction. The IoC is effective in monitoring the sedative effects of ciprofol when responsiveness disappears. The IoC is an effective monitoring tool for monitoring the sedative effects of ciprofol-induced general anesthesia. Trial registration ChiCTR2400086320.